Dari Bertahan Menuju Bertumbuh:Peran Human Capital Pegadaian dalam Transformasi Nasabah Gadai Menjadi Investor Emas - Sri Astuti Nasir; Indri Iswardhani; Nulthazam Sarah; Nur Fadilah Ayu Sandira; Josafat Gracia Ginting (Jurnal Online Manajemen ELPEI, 2026)
This study investigates the strategic role of human capital at Pegadaian in transforming customers from a survival-oriented mindset—where gold is perceived merely as a collateral instrument during emergencies—toward a growth-oriented mindset in which gold is understood as a long-term investment asset. Using a qualitative exploratory design, the research is based on in-depth interviews with ten customers who transitioned from pawn service users to gold investors. The findings reveal that this transformation is mediated by Pegadaian employees who act as financial change agents. Three key mechanisms are identified. First, employees build trust by leveraging relationships previously established through pawn transactions. Second, they provide contextualized financial education that bridges traditional perceptions of gold with modern investment concepts. Third, they offer continuous assistance throughout the gold investment process. The results demonstrate that the success of financial institution transformation largely depends on the capacity of its human capital to function as translators of financial culture. Their role extends beyond increasing financial literacy to reshaping customers’ economic behavior from short-term consumption toward long-term wealth accumulation. This study highlights that employee competency development serves as a crucial driver of customer financial literacy and inclusion.